The influence of droplet size on the stability, in vivo digestion, and oral bioavailability of vitamin E emulsions. Issue 5 (22nd April 2016) - Parthasarathi, S.; Muthukumar, S. P.; Anandharamakrishnan, C.
Abstract : Vitamin E (α-tocopherol) is a nutraceutical compound, which has been shown to possess potent antioxidant and anticancer activity. Abstract : Vitamin E (α-tocopherol) is a nutraceutical compound, which has been shown to possess potent antioxidant and anticancer activity. However, its biological activity may be limited by its poor bioavailability. Colloidal delivery systems have shown wide applications in the food and pharmaceutical industries to deliver lipophilic bioactive compounds. In this study, we have developed conventional and nanoemulsions of vitamin E from food grade ingredients (sunflower oil, saponin, and water) and showed the nanoemulsion formulation increased the oral bioavailability when compared to the conventional emulsion. The mean droplet diameters in the nano and conventional emulsions were 0.277 and 1.285 μm, respectively. The stability of the emulsion formulation after thermal processing, long-term storage at different temperatures, mechanical stress and in plasma was determined. The results showed that the saponin coated nanoemulsion was stable to droplet coalescence during thermal processing (30–90 °C), long-term storage and mechanical stress when compared to the conventional emulsion. The biological fate of the emulsion formulations were studied using male Wistar rats as an animal model. The emulsion droplet stability during passage through the gastrointestinal tract was evaluated by their introduction into rat stomachs. Microscopy was used to investigate the structural changes that occurred during digestion. Both the conventional emulsion and nanoemulsion formulations showed strong evidence of droplet flocculation and coalescence during in vivo digestion. The in vivo oral bioavailability study revealed that vitamin E in a nanoemulsion form showed a 3-fold increase in the AUC when compared to the conventional emulsion. The information reported in this study will facilitate the design of colloidal delivery systems using nanoemulsion formulations.